The development and evaluation of a self-marking unit to estimate malaria vector survival and dispersal distance - Saddler, Adam (Malar J, 2019)
BACKGROUND: A clear understanding of mosquito biology is fundamental to the control efforts of mosquito-borne diseases such as malaria. Mosquito mark-release-recapture (MMRR) experiments are a popular method of measuring the survival and dispersal of disease vectors; however, examples with African malaria vectors are limited. Ethical and technical difficulties involved in carrying out MMRR studies may have held back research in this area and, therefore, a device that marks mosquitoes as they emerge from breeding sites was developed and evaluated to overcome the problems of MMRR. METHODS: A modified self-marking unit that marks mosquitoes with fluorescent pigment as they emerge from their breeding site was developed based on a previous design for Culex mosquitoes. The self-marking unit was first evaluated under semi-field conditions with laboratory-reared Anopheles arabiensis to determine the marking success and impact on mosquito survival. Subsequently, a field evaluation of MMRR was conducted in Yombo village, Tanzania, to examine the feasibility of the system. RESULTS: During the semi-field evaluation the self-marking units successfully marked 86% of emerging mosquitoes and there was no effect of fluorescent marker on mosquito survival. The unit successfully marked wild male and female Anopheles gambiae sensu lato (s.l.) in sufficiently large numbers to justify its use in MMRR studies. The estimated daily survival probability of An. gambiae s.l. was 0.87 (95% CI 0.69–1.10) and mean dispersal distance was 579 m (95% CI 521–636 m). CONCLUSIONS: This study demonstrates the successful use of a self-marking device in an MMRR study with African malaria vectors. This method may be useful in investigating population structure and dispersal of mosquitoes for deployment and evaluation of future vector control tools, such as gene drive, and to better parameterize mathematical models.